2008
DOI: 10.1136/jnnp.2007.133132
|View full text |Cite
|
Sign up to set email alerts
|

Long-term occurrence of death and cardiovascular events in patients with transient ischaemic attack or minor ischaemic stroke: comparison between arterial and cardiac source of the index event

Abstract: Our study shows that the long term risk of death or vascular events is 1.5 times higher in patients with CIAF than in those with CIAO, after adjustment for differences between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…The overall increased short- and long-term mortality among patients with atrial fibrillation in our study is consistent with a number of other studies 411,44. Different mechanisms have been suggested to underlie the increased mortality, yet no definitive answer has emerged.…”
Section: Discussionsupporting
confidence: 88%
“…The overall increased short- and long-term mortality among patients with atrial fibrillation in our study is consistent with a number of other studies 411,44. Different mechanisms have been suggested to underlie the increased mortality, yet no definitive answer has emerged.…”
Section: Discussionsupporting
confidence: 88%
“…In the Dutch TIA Trial [26] 60% had died after 10 years, while in the present study 74% of participants with ischemic stroke had died at 10 years, which reflects that our sample was population-based and also included the severest stroke patients, while the Dutch population consisted of patients with TIAs and minor stroke.…”
Section: Discussionmentioning
confidence: 81%
“…Some authors have shown that a recent infarct on CT scan increases significantly the 90-day risk of stroke [14]. Other factors such as atrial fibrillation [15] and the type of stroke [13] were implied in an increased risk. About this latter point atherosclerotic seems to carry a substantial risk of stroke [13].…”
Section: Introductionmentioning
confidence: 97%